Proceedings of the 10th ACM Conference on Web Science 2019
DOI: 10.1145/3292522.3326039
|View full text |Cite
|
Sign up to set email alerts
|

Characterising Third Party Cookie Usage in the EU after GDPR

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 8 publications
2
15
0
Order By: Relevance
“…We add to a growing empirical literature on technical and commercial implications of the GDPR, and relate to theoretical work on its implications for competition policy. This literature spans across disciplines, including industry reports (WhotracksMe, 2018), and academic work in computer science and communication (Dabrowski et al, 2019;Solomos et al, 2019;Hu and Sastry, 2019;Degeling et al, 2018;Libert et al, 2018;Sørensen and Kosta, 2019;Urban et al, 2020), marketing (Johnson and Shriver, 2020;Goldberg et al, 2019;Goddard, 2017), information systems and economics (Godinho de Matos and Adjerid, 2020;Zhuo et al, 2019;Sharma et al, 2019;Lefrere et al, 2019;Jia et al, 2019b,a;Aridor et al, 2020), and law (Gal and Aviv, forthcoming;Geradin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…We add to a growing empirical literature on technical and commercial implications of the GDPR, and relate to theoretical work on its implications for competition policy. This literature spans across disciplines, including industry reports (WhotracksMe, 2018), and academic work in computer science and communication (Dabrowski et al, 2019;Solomos et al, 2019;Hu and Sastry, 2019;Degeling et al, 2018;Libert et al, 2018;Sørensen and Kosta, 2019;Urban et al, 2020), marketing (Johnson and Shriver, 2020;Goldberg et al, 2019;Goddard, 2017), information systems and economics (Godinho de Matos and Adjerid, 2020;Zhuo et al, 2019;Sharma et al, 2019;Lefrere et al, 2019;Jia et al, 2019b,a;Aridor et al, 2020), and law (Gal and Aviv, forthcoming;Geradin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A simple Web crawler visiting the websites without accepting the privacy policies would offer a biased picture, with no trackers and no ads being loaded. Hu et al [35] already found that the number of third-parties dropped by more than 10% after GDPR when visiting websites automatically. Conversely, when using a dataset from 15 real users, they measure no significant reduction in long-term numbers of third-party cookies.…”
Section: The Effect Of Privacy Banners On Web Measurementsmentioning
confidence: 99%
“…Interestingly, many websites correctly implement the regulations, and they activate trackers and personalized ads only after consent is collected. This makes the illusion that tracking is decreasing with respect to the past [35]. However, the number of trackers websites embed substantially increases upon acceptance of the privacy policy, in some cases up to 70.…”
mentioning
confidence: 99%
“…Researchers using the GDPR as a standard to assess compliance to the law have found that while there was some observed reduction on the amount of tracking since the law went into effect, this did not translate generally [27]. In fact, while websites gave users a glanceable means of determining compliance to GDPR via "levelled choices" on their tracked activities [14], the websites tracked the users anyways-before, and even after the user has stated their preferences against being tracked. This direct contravention of both the letter and the spirit of the GDPR laws was observed to be especially prevalent in news sites whose revenues are primarily based on advertising [8].…”
Section: 2mentioning
confidence: 99%